Bibliometric Analysis of Publications on Decentralization and Social Policy - Cobos-Alvarado, Fabian; Peñaherrera-León, Mónica; Alvarado, Juan Carlos Merchán; Valle , Benjamín Wilson León; Saavedra-Palma, Jorge Enrique (Journal of Ecohumanism, 2024)
This article presents a bibliometric analysis of articles in Scopus on “decentralization” and “social policy”, using the tools Vosviewer and Bibliometrix. The introduction highlights the growing importance of these areas in academic research and the need for rigorous methods to assess their evolution. The aim of the study is to quantify and validate categories related to these topics in order to obtain an objective and detailed perspective of current trends in the literature. The methodology employed includes the collection and analysis of bibliographic data from Scopus using specialized tools to map collaboration networks and emerging areas of research. The results indicate that bibliometric methods are effective in measuring and validating research categories that could be subjective in traditional reviews. In addition, they facilitate the exploration of new areas and allow the identification of emerging categories in the study of decentralization and social policy.